Meridional Connectivity of a 25‐Year Observational AMOC Record at 47°N - Simon Wett; Monika Rhein; Dagmar Kieke; Christian Mertens; Martin Moritz (Geophysical Research Letters, 2023)
Abstract Since climate model studies project a decline of the Atlantic Meridional Overturning Circulation (AMOC) in the 21st century, monitoring AMOC changes remains essential. While AMOC variability is expected to be coherent across latitudes on longer than decadal timescales, connectivity on inter‐annual and seasonal timescales is less clear. Model studies and observational estimates disagree on the regions and timescales of meridional connectivity and AMOC observations at multiple latitudes are needed to study its connectivity. We calculate basin‐wide AMOC volume transports (1993–2018) from measurements of the North Atlantic Changes (NOAC) array at 47°N, combining data from moored instruments with hydrography and satellite altimetry. The mean NOAC AMOC is 17.2 Sv exhibiting no long‐term trend. Both the unfiltered and low‐pass filtered NOAC AMOC show a significant correlation with the RAPID‐MOCHA‐WBTS AMOC at 26°N when the NOAC AMOC leads by about one year.